Prefigurative Politics and Cultures of Care in the Portuguese Youth Climate Strike Movement during School Occupations - Rebelo, Dola; Malafaia, Carla; Fernandes-Jesus, Maria (PARTECIPAZIONE E CONFLITTO, 2025)
Young climate activists draw inspiration from diverse social and political struggles and use several tactics and strategies of collective action to build their movements. Extant scholarship on youth climate activist groups such as the School Strike for Climate have focused on how young people organise and set up their political priorities to tackle the climate crisis. However, there is still a lack of research on the inner dynamics and relationalities that sustain youth-led climate movements. To better understand how young climate activists mobilise during collectively intense and demanding periods of protest, it is important to explore their everyday practices and modes of conviviality. This article offers a contribution in this regard, drawing on an ethnographic study conducted before, during and after the occupation of five high schools and seven universities in Lisbon, in May and November 2023, by the Portuguese chapter of School Strike for Climate, to examine the interconnections between prefigurative politics and cultures of care, two scholarship strands requiring closer bridging. Our findings show that youth climate movements are shaped by cultures of care and political aspirations that help create more hopeful futures for young people. Prefiguration can be used both as a tool and an activism practice that helps to forge and actualise the movement's claims and purposes.